Adela Breton : a Victorian artist amid Mexico's ruins - McVicker, Mary Frech (University of New Mexico Press, 2005)
Mary McVicker relates the story of Adela Breton, a Victorian gentlewoman who spent a lifetime of travel, exploring past cultures and landscapes in Mexico. She tells of her independence from the strictures of Victorian life, as well as her career as an artist-archaeologist and the significance of her work.